Characterization of prostatic ultrasonographic abnormalities in dogs treated in a veterinary clinic in Lima, Peru from 2010 to 2014 - Ygreda, Gabriela (2017)
The aim of this study was to characterize the prostatic ultrasonographic alterations in dogs treated at the Veterinary Clinic Cayetano Heredia (Lima, Peru), during 2010 to 2014, correlating the observed alterations with diagnoses compatible to prostatic pathologies, considering the size, age and breed. A total of 407 clinical histories of patients that presented one or more prostatic alterations were evaluated, being the adult dogs of small size and purebred the most affected population, and the prostatomegaly was the most common condition. Benign prostatic hyperplasia and prostatic neoplasias were the predominant anatomopathologic alterations. Prostatic alterations can also be seen in young animals. The results reaffirm that the ultrasonography allows the identification of the most frequent prostatic pathologies.